Consensus conference results on contraception in women beyond 40 years of age - Cagnacci, Angelo; Fruzzetti, Franca; Bruni, Vincenzina; Gambera, Alessandro; Guida, Maurizio; Bonaccorsi, Gloria; Londero, Ambrogio Pietro (The European journal of contraception & reproductive health care, 2025)
The objective is to develop expert consensus to inform clinical decision-making in the use of hormonal contraceptives in women over 40 years of age. A multidisciplinary panel organised by the Italian Society of Contraception performed a systematic literature review up to October 2024, defining the priorities in the choice of a contraceptive and its effects on cardiovascular risk, menstrual bleeding, bone health, and sexual function associated with hormonal contraception in women over 40. Statements summarising the findings were discussed and refined in a dedicated expert meeting. Final statements were presented and subjected to anonymous voting at a national congress, where consensus was defined as a minimum of 75% agreement. Ninety-five to ninety-nine percent of participants endorsed seven consensus statements. Cardiovascular safety is recognised as the primary factor in the selection of contraceptives. The use of progestogen-only methods is considered safe for cardiovascular risk. Combined hormonal contraceptives utilising natural oestrogens or 20 mcg ethynylestradiol in conjunction with non-androgenic progestins are considered more advantageous for the cardiovascular risk profile. The levonorgestrel intrauterine device, oestradiol valerate/dienogest, and the combined contraceptive vaginal ring are identified as the most effective options for menstrual management. The type of hormone and its route of administration can influence sexual function, with implants and vaginal rings showing positive effects. Combined hormonal contraceptives demonstrate protective effects on bone density, whereas progestogen-only methods exhibit a neutral impact. This Italian consensus provides evidence-based guidance on hormonal contraceptive choices for women over 40, incorporating non-contraceptive effects to support individualised care during perimenopause.